Study of Video Games as Alternative Teaching Media In Covid-19 Pandemic Era - Utomo, Pandu R (VCD: Journal of Visual Communication Design, 2021)
Technology has a direct impact on human’s behaviors and lifestyles in Covid-19 pandemic era. Various sectors such as education and economy adapted technology-based remote work and study. With the existence of remote study, the educational world will still face some issues related to the study effectiveness which requires students’ initiatives in the process. This research’s aim is to explore video game's potential as an alternative education method to solve those issues. Also, it is to study the reason why videogames are considered as a solution for remote study’s challenges during this pandemic. A study method towards related literature was used in this research. Conclusion achieved from this research is that videogames are able to stimulate students’ initiatives in exploring learning materials. Video games gave play-like learning experience and thus, reduced the stress on the students during remote study. However, the result still needs further study to achieve realistic methods that can be applied in the field. Keywords: Game, Remote Study, Pandemic